Design Aspects of Double Rig Shrimp Trawls Operated off Vishakhapatnam - K.N., Kartha; A.C., Kuttappan; M.D., Varghese; V.C., George; S.V.S., Rama Rao; H., Krishna Iyer (Fishery Technology, 2025)
Investigations were carried out to establish the empirical relationship between engine power and size of double rig trawl as well as interrelationship of its different parts and accessories. The empirical formula evolved to determine the above said relationships are presented in this communication. This study revealed that the double rig trawls operated off Vishakhapatnam has undergone changes with respect to wing and body since its introduction.